The preliminary psychometric properties of measuring tools for identifying transformational leaders in education - Heinzová, Zuzana (Psihološka obzorja (Ljubljana), 2022)
School transformation is a real process that is happening all over the world and also in Slovakia. Recently, one of the important topics involved in it is the conceptualisation and measurement of educational leadership. The purpose of this study was to examine the preliminary psychometric properties of the Slovak forms of the Leadership Practices Inventory (LPI; Kouzes & Posner, 2012) and the Czech Leadership Questionnaire (CLQ; Procházka et al., 2016) and to ,provide a culturally appropriate instrument for Slovak teachers. The study presents the results of the validation under Slovak conditions. The research sample consisted of teachers from different regions of Slovakia. The preliminary psychometric examinations used reliability and construct validity of internal consistency and suggest that both tools appear to be useful in identifying transformational leaders in education. The study is limited by non-standardised tools, research sample specifics, and sampling.
Keywords: Češki vprašalnik vodenja CLQ; Lestvica vodstvenih praks LPI; psihometrija; veljavnost; vodenje; vzgoja; zanesljivost testa; zobraževanje